Prevalence and Associated Factors of Hypertension among Civil Servants Working in Arba Minch Town, South Ethiopia - Aschenaki Kalssa; Gistane Ayele; Alemu Tamiso; Tadele Girum (Intelektual Pustaka Media Utama, 2016)
Despite Hypertension is a global public health challenge and a leading modifiable risk factor for cardiovascular disease and death attention was not given in developing countries. Therefore measuring the prevalence and identifying predictors of Hypertension is very important. Institution based cross sectional study design was employed from March–April, 2016 by taking 319 randomly selected civil servants working in in Arba Minch town. Data was collected using structured questionnaire and standardized instruments for physical examination by 5 trained nurses. SPSS version 20 was used for data analysis. Bi-variable and Multivariate logistic regression was employed for analysis of risk factors. The mean SBP and DBP of study participants were 120.87 + 14.15 mmHg and 80.28 + 8.8 mmHg, respectively. The prevalence of hypertension was found to be 27.8% (95% CI = 22.9-32.7%). Civil servants of age 50 years and above [AOR = 13.3], age 40-49 years [AOR = 5], age 30-39 years [AOR = 3.5], abdominal obesity [AOR=12.2], general obesity [AOR = 4.2], stress status [AOR = 12.3], current alcohol drink [AOR = 3.3], ex-drinker [AOR = 8.9] and family history of hypertension [AOR = 5.6] were found to be significantly associated with hypertension. The prevalence indicates that it is hidden epidemic in this population; therefore for screening and risk reduction program are needed.